Activity of Lintut (Strobilanthes kalimantanensis) Leaves Essential Oil as Anti-inflammatory in Male Mice (Mus musculus) - Susilowati, Kartika Indah; Prabowo, Wisnu Cahyo; Ahmad, Islamudin (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Inflammation is a natural response of body cause by strange substances that can damage the body cells and tissues. Lintut (Strobilanthes kalimantanensis) is an endemic plant from West Kutai which is used as a respiratory-lozenges. Lintut leaves have a distinctive aroma and contain alkaloids, terpenoids and phenols. This research aims to determine its anti-inflammatory activity, the best dose, and effectiveness as an anti-inflammatory. This research uses the croton oil induction method which is applied topically to the ears of mice. Mices are grouped into 5 groups, concentrations of 5%, 10%, 15%, negative control (acetone), and positive control (diclofenac sodium cream 1%). The research results obtained from this research are the results of weighing the ear, macroscopic images and microscopic images. The results of the percent edema obtained showed that only at a concentration of 10% the essential oil of lintut leaves had anti-inflammatory activity, namely with a percent edema value of 26.48%. This concentration was then compared with 1% diclofenac sodium cream. The statistic results show a significant difference, this shows that the 10% concentration has good effectiveness as an anti-inflammatory.